A Descriptive Study of Internet-enhanced Instruction in Georgia Secondary Agricultural Education - Parks, Walter J. (My University, 2018)
The purpose of this study was to describe the extent and type of the use of Internet-enhanced instruction by secondary Agricultural Education teachers in Georgia, to determine perceived barriers and enabling factors for the implementation of such instruction and provide insight into the kinds of professional development Agricultural Education teachers need. Demographic information on each program was used to determine if differences existed in relation to Internet usage. Data were collected using a survey instrument for the quantitative portion and semi-structured interviews for the qualitative portion. Descriptive statistics were used to analyze responses to the survey instrument and frequencies and percentages were reported. Multivariate Analysis of Variance tests were used to determine if significant differences on the perceptions of respondents towards using the Internet to enhance learning in the classroom could be attributed to ratings on the survey in relation to the demographic variables of age, years of teaching experience, number of hours using the Internet per week, and the number of Internet-connected devices in the respondents’ rooms. Open-ended questions were utilized during the interview process to identify perceived barriers and enablers and elicit recommendations for professional development. The findings revealed that 98% of participants used the Internet to some degree to enhance learning in their classrooms. There was a significant effect on survey ratings for the variables of age, total years teaching, and the number of Internet-connected devices. Teachers selected for interviews shared many recommendations for professional development, the most prominent of which was to focus on one Internet use at a time.
Chapter I: INTRODUCTION 1 | Statement of the Problem 6 | Purpose of the Study 6 | Research Questions 7 | Theoretical Framework 7 | Limitations 9 | Assumptions 10 | Significance of the Study 10 | Definition of Key Terms 11 | Chapter II: LITERATURE REVIEW 14 | Introduction 14 | Theoretical Framework 15 | History of Internet integration in the classroom 19 | Internet-enhanced instruction at the Post-secondary level 24 | Internet-enhanced instruction in Secondary Academic disciplines 25 | Internet-enhanced instruction in CTE and Agricultural Education 25 | Barriers to Technology Integration 26 | Summary 27 | Chapter III: RESEARCH METHODOLOGY 29 | Introduction 29 | Statement of the Problem 29 | Purpose of the Study 29 | Research Questions 30 | Significance of the Study 30 | Research Design 31 | Population and Sample 33 | Instrumentation 34 | Survey Data Collection 34 | Interview Data Collection 46 | Research Procedures 47 | Survey Data Analysis 50 | Demographic Analysis 50 | Research Question One Data Analysis 50 | Research Question Two Data Analysis 51 | Research Question Three and Four Data Analysis 51 | Research Question Five Data Analysis 52 | Interview Data Analysis 53 | CHAPTER IV: FINDINGS 55 | Introduction 55 | Review of Research Questions 56 | Section One: Online Survey Results 56 | Demographic Data Analysis 56 | Summary of Demographic Findings 64 | Extent of the Use of Internet-enhanced Instruction 65 | Current Uses of Internet-enhanced Instructional Strategies 70 | Factors that Encourage or Discourage Internet-enhanced Instructional Strategies 72 | Demographic Factors 72 | Intrinsic Factors and Variables 84 | Multivariate Analysis of Variance 88 | Years of Age 92 | Years Teaching Experience 93 | Internet-Connected Devices in the Classroom 95 | Professional Development Opportunities Needed 97 | Section Two: Results of the Interviews 98 | Qualitative Interview Findings 98 | Interview Analysis of Extent of the use of Internet-enhanced Instruction 101 | Interviewee’s Current Uses of Internet-enhanced Instructional Strategies 102 | Contest (CDE) Preparation 103 | Student Assessment 104 | Record Keeping 104 | Student-focused Lessons 105 | Teacher-focused Lessons 107 | Interviewees’ Comments on Factors that Encourage or Discourage the Use of Internet-enhanced Instructional Strategies 108 | Years of Teaching Experience 108 | Availability of Internet-connected Devices 110 | Technical Difficulties 113 | Time 114 | Student Distraction 114 | Desire for Hands-on Learning 115 | Unique Responses 116 | Effectively Engaged Students 117 | Made Teaching Easier and More Efficient 117 | Interviewees’ Interpretation of and Suggestions for Professional Development 119 | How to Encourage Older Teachers to Use the Internet to Enhance Learning 119 | Where Interviewees Learned How to Use the Internet to Enhance Learning 121 | Recommendations for Professional Development 125 | Summary of Findings 127 | Chapter V: CONCLUSIONS AND RECOMMENDATIONS 130 | Introduction 130 | Research questions 131 | Conclusions 132 | Recommendations for Professional Development 139 | Recommendations for Future Research 141 | Final Significance 142 | REFERENCES 145 | APPENDIX A: IRB Approval from Valdosta State University 157 | APPENDIX B: Survey Instrument 159 | APPENDIX C: Validation of Survey Instrument 174 | APPENDIX D: Permission to Modify and Use Existing Survey 176 | APPENDIX E: Original Survey Instrument 178 | APPENDIX F: E-mail Letter to Participants/Informed Consent 184 | APPENDIX G: E-mail Letter to Telephone Interview Participants 186 | APPENDIX H: Interview Questionnaire 188 | APPENDIX I: Interview Responses 193 | APPENDIX J: Interview Transcripts 210 |
Keywords: Agricultural education; Web-based instruction; Computer-assisted instruction; Georgia. Career, Technical, and Agricultural Education.; Education